Perubahan Perilaku Tanah Lempung Lunak Akibat Stabilisasi dengan Bahan Aditif Kapur menggunkaan Metode Deep Soil Mixing Pola Triangular - Pangestu, Beno Balakosa; Iswan, Iswan; Putra, Andius Dasa (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2021)
Pelembapang, South Lampung has a soft clay soil structure. Soft clay soil has a low bearing capacity value This has an effect on the building to be built on it. Therefore, soil stabilization must be carried out. The method used in this study is the deep soil mixing (DSM) method, which is one of the soil improvement method by mixing additional materials in the field (in-site). This method is more affordable because they use their soil as theiraggregate and reduce the transportation budget because of stuff supply.The purpose of this study is to determine the change of soil load-bearing capacity due to the variation of distance and the diameter of the DSM stabilization column on soft clay soil and soft clay soil with 8% lime. This study shows that the stabilization of soft clay soil using DSM of 8% lime with triangular configuration has increased its load-bearing capacity (qu) from10.368 kg/cm2 to 12.96 kg/cm2. The increase of soil load-bearing capacity with the stabilization of the DSM column is proportional to the volume of soil improvement. The largest increase of the soil load-bearing capacity occurred in 1D columns range and 3.75 cm diameter. The distance variation also gives a more significant change compared to the variation of diameter. The most efficient distance and diameter are at the variation of the distance of 1.25D columns range and 2.5 cm diameter.